PENGARUH EXPRESSIVE WRITING THERAPY TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI - Baharudin Lutfi; Yani Sriyani; Wulan Rahmaniati (LPPM Universitas Bakti Tunas Husada, 2022)
Surgery is one of the many medical treatments performed regularly invasive, preoperative patients often experience anxiety which can cause harm to preoperative patients both physical, psychological, and administrative. Management to reduce anxiety levels in preoperative patients is one of them with psychotherapy. This study aims to determine the effect of expressive writing therapy on the level of anxiety of preoperative patients in the Jasmine 4 inpatient room at Soekardjo General Hospital, Tasikmalaya City. The research design used a pretest-posttest one group design with a sample of 21 respondents. The sampling technique was accidental sampling. The instrument for assessing the level of anxiety used the Zung Self-rating Anxiety Scale (ZSAS) questionnaire. The data analysis of the anxiety level score before and after being given expressive writing therapy was carried out by using the Paired t-test statistical test. The results show that there is an effect of expressive writing therapy on anxiety levels with p-value = 0.000 < ɑ (0.05). This study serves as an evidence-based practice in the application of expressive writing therapy as an intervention in the management of anxiety in preoperative patients.